2008
DOI: 10.1086/590008
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology, Clinical Features, and Long‐Term Prognosis of Japanese Encephalitis in Central Sarawak, Malaysia, 1997–2005

Abstract: Neurological assessment of Japanese encephalitis survivors at hospital discharge does not predict long-term outcome. Seizures and shock are treatable risk factors for a poor outcome at hospital discharge and at long-term follow-up visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
79
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 16 publications
10
79
3
2
Order By: Relevance
“…9 Long hospital stay was also associated with poor prognosis in the present study and most likely reflects the severity of the disease. Other factors that reflect severity of disease, such as low Glasgow Coma Scale score on admission, 15,28,37 deep coma, 28 and ICU admission, 14 were previously found as poor prognostic factors in other studies (although not in the present study). Several authors have suggested that young age is associated with a poor long-term prognosis in children with encephalitis.…”
Section: Figuresupporting
confidence: 55%
See 2 more Smart Citations
“…9 Long hospital stay was also associated with poor prognosis in the present study and most likely reflects the severity of the disease. Other factors that reflect severity of disease, such as low Glasgow Coma Scale score on admission, 15,28,37 deep coma, 28 and ICU admission, 14 were previously found as poor prognostic factors in other studies (although not in the present study). Several authors have suggested that young age is associated with a poor long-term prognosis in children with encephalitis.…”
Section: Figuresupporting
confidence: 55%
“…(28) brain tumor, 24 was previously reported, little is known about its association with infectious encephalitis. Behavioral anomalies similar to ADHD were first described as a complication of encephalitis after the influenza epidemic of 1918.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In our study, GCS score below 8, concurrent seizure and coma at the time of admission were found to be poor prognostic factor and associated with increased mortality. Similar observations were made by various workers in their earlier studies, Ooi MH et al(2008) in Malaysia , Y C Wu et al (1999) in Taiwan (13,14).…”
Section: Original Research Article Clinical Profile and Outcome Of Psupporting
confidence: 89%
“…During follow-up, 31 patients experienced improvement, but 15 patients experienced deterioration in their outcome grade. 15 Japanese Encephalitis (JE) disability assessment, Cambodia, 2007-2008, reported that out of 54 survivors five (10.6%) had severe sequelae, eighteen (38.3%) and twenty one ( 44.7 %) of children had moderate and mild sequelae, respectively. Only three children (6.4%) were considered to have recovered completely to a comparable condition as prior to illness.…”
mentioning
confidence: 99%